Evaluation of National Health Assurance Service Quality - Aila Karyus; Febria Listina; Zahratul Fauziyah (GLOBAL HEALTH SCIENCE GROUP, 2021)
Patient satisfaction is the response of patients to the suitability of the level of patient expectations before and after they receive the services. One way that can be done to measure community satisfaction with government services is to use a community satisfaction survey. This study aimed to determine the quality of JKN services in Demang Sepulau Raya Central Lampung Hospital. The type of research used was quantitative. The population in this study amounted to 764 respondents. These respondents were selected from the JKN data as a whole, then selected n (data) is active, the sample of this study was 96 respondents. Based on the data analysis and research results, the IKM value of JKN service quality in Demang Sepulau Raya Central Lampung Hospital according to the requirements element was 84.11% (Very Good), procedure was 79.43% (Good), implementation time was 79.69% (Good), cost/tariff was 78.65% (Good), product specifications was 77.08% (Good), implementing competence was 84.38% (Very Good), implementing behavior was 76.56% (Good), notice services was 78.65% (Good), and for all elements was 79.83% (Good). The quality of service that needs to be improved is an indicator of service competence, implementing and socializing the concept of an effective and responsive customer complaint handling system, so patients are not reluctant to submit their complaints because they know for sure that the complaint will be followed up.